2020
DOI: 10.3390/cells9010137
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Based Therapeutics: From Antisense Oligonucleotides to miRNAs

Abstract: The first therapeutic nucleic acid, a DNA oligonucleotide, was approved for clinical use in 1998. Twenty years later, in 2018, the first therapeutic RNA-based oligonucleotide was United States Food and Drug Administration (FDA) approved. This promises to be a rapidly expanding market, as many emerging biopharmaceutical companies are developing RNA interference (RNAi)-based, and RNA-based antisense oligonucleotide therapies. However, miRNA therapeutics are noticeably absent. miRNAs are regulatory RNAs that regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
211
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(233 citation statements)
references
References 204 publications
(214 reference statements)
0
211
0
Order By: Relevance
“…Our study has indicated the melanoma cells are highly vulnerable to the decrease in K1, suggesting that K1 may be a novel valuable target for treating melanoma cells. RNAi approach has become a promising technology for treating multiple diseases [1]. It is expected that RNAi approach is capable of producing at least a mild decrease in the K1 levels of melanoma cells, which may produce therapeutic effects on melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has indicated the melanoma cells are highly vulnerable to the decrease in K1, suggesting that K1 may be a novel valuable target for treating melanoma cells. RNAi approach has become a promising technology for treating multiple diseases [1]. It is expected that RNAi approach is capable of producing at least a mild decrease in the K1 levels of melanoma cells, which may produce therapeutic effects on melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of miR-927 was performed in C6/36 cells at 57 weeks of persistent infection with DENV-2 (C6-L57 cells) or in non-infected C6/36 cells using the miR-927 inhibitor (assay ID: MH17622) and miRNA inhibitor control number 1 as a non-related miRNA control. The miRNA-927 inhibitor is a chemically modified RNA complementary molecule that binds specifically to miR-927, preventing its binding to target mRNAs [26].…”
Section: Mir-927 Inhibition and Overexpression Assaysmentioning
confidence: 99%
“…Manipulation of the expression levels of mRNAs targeting intracellular pathways involved in physiologic and/or pathologic processes might represent novel powerful therapeutic treatment options [ 159 , 160 ]. A snapshot of the current developmental status of targets of miRNA- and RBP-based modulators and connected therapeutics and their targets in MDS and sAML is summarized in Table 4 .…”
Section: Treatment Options Of Mrna Binding Modulators In Mds Andmentioning
confidence: 99%
“…However, it is encouraging that the first small-interfering RNA (siRNA) drug Onpattro ® (patisiran), a therapy for the rare hereditary disease transthyretin-mediated amyloidosis in adult patients, was approved by the Food and Drug Administration (FDA) and the European Medicines Agency (EMA) [ 196 , 197 ]. Furthermore, a number of miRNA vaccine therapies are currently in the clinical development or in phase I/II trials, while others were halted due to severe side effects [ 159 ]. The possibilities in the implementation of miRNAs as treatment option are rapidly progressing in a wide range of diseases alone or in combinations with other therapeutic agents affecting genetic and epigenetic targets.…”
Section: Therapeutic Possibilities Of Mirnas In Mds and Samlmentioning
confidence: 99%